EP1065 Comparison of two self-sampler devices for cervical screening in a South African population. (1st November 2019) - Breidenthal, A; van der Merwe, FH; Dreyer, G; Snyman, L; Visser, C; Botha, MH
Abstract : Introduction/Background: Self-sampling is an attractive addition to cervical screening programmes. It can remove barriers to testing as some women fear a gynaecological examination, and offers potential task shifting and resource savings for overburdened health care systems often in low resource settings. Methodology: We performed a large cervical cancer screening study with ultimate objective to determine optimal screening algorithms for South African women. This interim analysis describes the experiences of a subset of women who were asked to fill in a questionnaire about the self-samplers. The aim was to compare user experiences of two different self-samplers in a South African public sector setting. 253 participants received a short education by the Health Care Worker (HCW), and were given either the Digene HC2 DNA Collection Device (Qiagen)or the Evalyn® Brush (Rovers Medical). Participant and HCW filled in a questionnaire afterwards. Results: Analysis was done for 253 women. Mean age in group was 41.33 years (range [24–63], median 41 years). 82 women were in the Digene group, and 171 in the Evalyn group. HCWs reported more bleeding with the Digene vs. Evalyn users (37.9% vs. 20.4%). Both groups felt it was very or somewhat easy to use (98.8% vs. 94.2%). Women had little fear of using the devices, (61.0% vs 71.3%), and felt sure of how to use them. There was more bleeding reported by Digene vs Evalyn users (9.8% vs. 4.1%), and lastly, there was little pain experienced by users of either brush, 91.5% vs 93.6%. Conclusion: In this cohort, both the self-samplers were well tolerated; there was more bleeding associated with use of the Digene device, both seen by participants and HCW, which will be analysed further once results are available. Self-sampling is feasible and acceptable in this public setting. Disclosure: Rover BD donated Evalyn brushes for the study, and Qiagen provided digene collection devices, but neither were involved in preparing papers.